An audit of the provisional date of elective surgery allotted to pediatric surgery outpatients of a tertiary care, public-funded teaching hospital of North India - Sachit Anand (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to review the compliance to the provisional date of elective surgery allotted to pediatric surgery outpatients at our center. Patients and Methods: This retrospective study was conducted in the department of pediatric surgery at our center. The children who were brought to the outpatient department with a previously allotted date of admission for elective surgery (DAES) and the final operation theater (OT) lists of elective surgery between July 2007 and September 2018 under one senior consultant (VB), were reviewed. Results: A total of 2409 cases were allotted a DAES during the study period. Out of these, 12% (288/2409) were defaulters with a male gender preponderance (82%). Most of the defaulters (>49%) belonged to the day-care surgery group, followed by simple reconstructive (32%), major reconstructive (18%), and infectious sequelae groups (<1%). The difference in the proportion of defaulters from both the reconstructive groups was statistically significant (P = 0.0001). On a further system-wise subcategorization of children in the day-care group, the genitourinary subgroup constituted the majority (80%). Children who had to undergo staged procedures showed a significantly better compliance (P < 0.0001) to provisional DAES as compared to those belonging to the single-stage group. Conclusions: Compliance to provisional DAES is poor among the children scheduled for day-care surgeries and those undergoing simple reconstructive surgeries in a single stage.